A stochastic inventory model with perishable and aging items. (1999) - Aggoun, Lakhdar; Benkherouf, Lakdere; Tadj, Lotfi
Abstract : In this paper, we propose a single-product, discrete time inventory model for perishable items. Inventory levels are reviewed periodically and units in stock have a maximum lifetime of M periods. It is assumed that the dynamics of the inventory level is driven by a parameter process (reflecting perishability) and demands. By observing the history of the inventory level we obtain the conditional distribution of the perishability parameter by using the change of measure techniques. A special case is also presented.